Effectiveness of Electronic Law Enforcement in Reducing Traffic Violations : Empirical Evidence from Gowa Regency, Indonesia - Marwati Basri; Nurul Qamar; Baharuddin Badaru (Manunggal Halim Jaya, 2025)
The primary aim of this study is to identify, analyze, and evaluate the effectiveness of the Electronic Ticketing system in reducing traffic violations in Gowa Regency. Additionally, it identifies the factors affecting both the success and the challenges of Electronic Ticketing implementation, using Soerjono Soekanto’s theory of legal effectiveness as the analytical framework. This study employs an empirical juridical approach with a qualitative design. Data were collected through literature review, interviews with Gowa District Traffic Police officers (Satlantas Polres Gowa), field observations, and documentation of relevant secondary data. This approach provides a comprehensive picture of the implementation of manual ticketing and the electronic traffic ticket system in practice. The findings show that manual ticketing during the 2022–2024 period was less effective in reducing traffic violations. By contrast, since its introduction in 2025, the Electronic Ticketing system has been able to detect violations automatically, transparently, and accountably. Nevertheless, its effectiveness in reducing traffic violations remains suboptimal because of low public rates of ticket confirmation and fine payment, incomplete delivery of violation notices by the police, and technological infrastructure limitations. Viewed through the perspective of legal effectiveness theory, the aspects of legal substance and legal structure have been met, but the factors of facilities, community, and legal culture still constitute major barriers. This study recommends strengthening regulations on administrative enforcement, optimizing Electronic Ticketing infrastructure, expanding public legal awareness campaigns, and enhancing inter-agency coordination to raise legal awareness. These measures would improve the effectiveness of electronic traffic ticket in reducing traffic violations and foster a disciplined and sustainable traffic law culture in Gowa Regency.